Identifikasi infeksi Koi Herpes Virus (KHV) pada ikan Koi (Cyprinus carpio) dengan metode Polymerase Chain Reaction (PCR), imunositokimia dan imunohistokimia - S. Edi .; O. Surfianti .; N. Christy .; R. Wiis .; Laminem .; E.R. Ekoputri .; M. Fathoni .; A. D. Koswara .; Nurhaidin .; U. Yanuhar . (Hemera Zoa, 2010)
Koi herpes vivus (KHV) disease has been diagnosed in koi and goldfish, and KHV is believed to remain in the body of its host to survive so that goldfish have the potential us a carrier virus. The purpose of this test is to look for another alternative method in identzfiing a particular fish disease Koi Herpes Virus (KHV) that is more simple and practical, rapid, precise and accurate as well as the examination results are expected to match the other examination techniques. Sample testing activities are positively infected with KHV derivedfrom Blitar marked by the characteristics of the most visible of the lesions (injuries) is congestion, bleeding onjns or body, or hemorrhagic on the basis of dorsal fins, pectoral fin, and anal Jins and the operculum, necrosis and nodules (nodule) in the gills white. The result of the testing activities identijcation of KHV by PCR, IHC and ICC were by using PCR samples obtained 7 positive KHV with DNA quality between 1.83 to 1.98 and DNA quantity between 31 7.89 to 492.08 at 290 bp DNA bands. It can be concluded that the alternative examination or identification of infections of Koi Herpes Virus (KHV) in addition to the koifish using PCR, immunohistochemistry, also can be developed using immunocytochemistry method (Streptavidin Biotin) due to simpler procedures, work more practical, lower cost, faster time, precise and accurate target.